Analisis Koreksi Fiskal Atas Laporan Keuangan Komersial Untuk Menghitung PPH Badan Terutang Pada PT Yoezhadassah - Novia Cynthia Maradesa; Giovani Novilia Kategu (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
To find out whether the fiscal correction made by PT Yoezhadassah is in accordance with the applicable tax law and to find out the effect of fiscal corrections made on commercial financial statements on Corporate Income Tax payable at PT Yoezhadassah. The type of research used is qualitative using the exploration method, which is to describe a situation about to get saturated answers regarding fiscal corrections on commercial reports and the preparation of fiscal financial statements and the calculation of Corporate Income Tax at PT Yoezhadassah. Data obtained by researchers through in-depth interviews as well as documentation and observation studies. The results showed that the fiscal correction of the 2021 financial statements of PT Yoezhadassah was carried out through a negative fiscal correction of income of IDR 38,226,905,190 and expenses of IDR 39,661,451,100 on the company's income statement so that the company, which initially according to the commercial income statement, suffered a pre-tax loss of IDR 1,343,629,518 on the fiscal financial statements, resulted in a pre-tax profit of IDR 103,198,00. Corporation income tax payable by PT Yoezhadassah in 2021 is calculated based on profit from non-final income, namely income from transportation minus costs related to transportation. Corporate income tax payable in 2021 of PT Yoezhadassah after fiscal correction is IDR 21,287,761. PT Yoezhadassah in making fiscal corrections to income and expenses is in accordance with applicable tax laws. Based on the results of existing research, the advice that can be given to PT. Yoezhadassah is that as a taxpayer who earns income subject to final and non-final tax, it is advisable to make separate financial statements for final and non-final income so that the tax calculation can be done correctly. PT Yoezhadassah continues to pay attention to the recognition of costs and revenues that are final and non-final.